Employing immunohistochemical staining to labial minor salivary gland biopsies from patients with Sjogren's syndrome increases diagnostic certainty. (27th November 2020) - Trivedi, Apoorva; Cornejo, Kristine M.; O'Donnell, Patrick; Dresser, Karen; Deng, April
Abstract: Background: Sjogren's syndrome (SjS) is an autoimmune disease characterized clinically by dry eyes and dry mouth, and histopathologically by lymphocytic infiltrates in the salivary glands. Labial minor salivary gland biopsy (MSGB) is a major diagnostic test for SjS, deemed positive by a focus score of ≥1, meaning that ≥50 lymphocytes were found in 4 mm 2 tissue on hematoxylin and eosin (H&E)‐stained slides. The diagnosis can be challenging, and the above diagnostic criteria has low and variable sensitivity. Methods: We performed a retrospective study on MSGBs done for possible SjS. We compared the percent of MSGBs which met the histologic criteria by H&E stain alone and that with the addition of CD45, CD3, and CD20 immunohistochemical (IHC) staining for these patients. A total of 45 cases with complete data were analyzed. Results: Thirty‐five of the 45 patients had the diagnosis of Sjogren's syndrome (SjS+) based on ACR criteria. However, based on H&E staining alone, only 22/35 cases (63%) met the histologic criteria. After adding IHC staining with CD45, CD3, and CD20 to MSGBs of SjS + patients, 29/35 (83%) cases met the histological criteria for SjS. All MSGBs from patients without SjS had no significant lymphocyte infiltrate on either H&E or IHC stains. Conclusions: Immunohistochemical better identifies lymphocytic infiltrates in MSGB and increases diagnostic certainty. Due to high cost, their use should be restricted to cases where there is high clinical suspicion of SjS and negative H&E evaluation alone, or if the diagnosis is uncertain.